Salmonella Derby: A Comparative Genomic Analysis of Strains From Germany - González-Santamarina, Belén; García-Soto, Silvia; Hotzel, Helmut; Meemken, Diana; Fries, Reinhard; Tomaso, Herbert (Frontiers in Microbiology, 2021)
Salmonella enterica subspecies enterica serovar Derby (S. Derby) is one of the most frequent causes for salmonellosis in humans and animals. Understanding the genetic diversity of S. Derby, as well as the nature and origin of its resistance to antimicrobial treatment are thus the key to epidemiological control and surveillance. Here, we report an analysis of 15 S. Derby strains isolated from pig and cattle in slaughterhouses across Germany (2000-2015), which belonged to multilocus sequence types (ST) ST39, ST40 and ST682. Strains were compared to publicly available S. Derby sequence data of these three STs from Germany, comprising 65 isolates collected between 2004 and 2018 from different sources (i.e., pigs, humans, cattle, wild boar, and poultry). A total of 80 sequences (ST39=34, ST40=21, and ST682=25) were analyzed to assess genetic diversity, to identify virulence-associated and antimicrobial resistance genes (ARGs), and to characterize plasmid content. Strains belonging to all three STs were identified in each source examined. Strains with the same ST were closely related regardless of origin. Altogether, 72.5% of the isolates carried at least one resistance gene, furthermore ST40 carried most of the ARGs and the plasmid replicons. The IncI1 replicon was detected in eleven isolates, four of them carried IncI1 plasmid ST26 with clonal complex 2. The comparison of these four isolates with an IncI1 ST26 plasmid reported in 2010 from a German pig (JX566770), showed only variations in a region carrying different ARGs and mobile genetic elements. The strains of our collection had similar genetic diversity as the strains taken from the public database. Moreover, we found that strains harboring multidrug resistant IncI plasmid were found in different animal species, indicating that S. Derby may be implicated in the spread of antimicrobial resistance among animal species. Results may contribute to the knowledge about the diversity in S. Derby in Germany, which may be useful for the future surveillance and antimicrobial resistance of this serovar.